2023
DOI: 10.1002/advs.202207216
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine Nanoparticles Targeting Ferroptosis Mitigate Intervertebral Disc Degeneration Via Reactive Oxygen Species Depletion, Iron Ions Chelation, and GPX4 Ubiquitination Suppression

Abstract: Intervertebral disc degeneration (IVDD)‐induced lower back pain (LBP) is a common problem worldwide. The underlying mechanism is partially accredited to ferroptosis, based on sequencing analyses of IVDD patients from the gene expression omnibus (GEO) databases. In this study, it is shown that polydopamine nanoparticles (PDA NPs) inhibit oxidative stress‐induced ferroptosis in nucleus pulposus (NP) cells in vitro. PDA NPs scavenge reactive oxygen species (ROS), chelate Fe2+ to mitigate iron overload, and regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Using genetic variants associated with iron status and IVDD, our two-sample MR analyses showed that iron status had no causal relationships with IVDD. Although it is generally believed that iron status and intervertebral disc degeneration disorders are separate entities,several studies have suggested an association between iron and IVDD [23].…”
Section: Discussionmentioning
confidence: 99%
“…Using genetic variants associated with iron status and IVDD, our two-sample MR analyses showed that iron status had no causal relationships with IVDD. Although it is generally believed that iron status and intervertebral disc degeneration disorders are separate entities,several studies have suggested an association between iron and IVDD [23].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that a large number of mitochondria are indeed present in NPCs; these mitochondria are typically tubular, highly networked, and hypoxia-responsive 41 . Moreover, a growing body of evidence demonstrates that mitochondrial dysfunction leads to excessive death in NPCs through mechanisms such as apoptosis and ferroptosis 42 44 . Consequently, keeping mitochondrial health is essential for maintaining the physiological function of NPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with POCG-PEI600 nanoclusters promoted the phosphorylation of p38 in the MAPK signaling pathway (Figure 23G), leading to the activation of PGC-1𝛼 and subsequent mitochondrial biogenesis. Consequently, an increase in Allergic asthma Nf-ABT-199 [ 379] --≈220 48 -Disc degeneration PDA NPs [ 380] --160 -PDA Fibromyalgia Mo 2 C nanozyme [ 380] --11.445(thickness) -Mo 2 C nanozyme Inflammation HCE-AuNPs [ 326] --3-20 --Mitochondrial oxidative stress TPP-Se-CDs [382] -T P P ≈18.4 ± 0.5 22.3 Se-CDs Mitochondrial protection LC-CNS@NTA [383] --230 ± 10 -Lantana camara Oocyte protection CeO 2 NPs [ 384] ≈10 -Oxidative stress Pt@CNDs [ 221] --3 . 2 ± 0.5 −28.1 ± 0.4 -…”
Section: Other Diseasesmentioning
confidence: 99%